The Commute to Work and the Gender Wage Differential: International Analysis - Miller, Paul (Nova Science Publishers, Inc., 2013)
This paper examines the effects of commute time and commute distance on wages in the United States and Canada, and the impact these have on the gender pay gap. Separate analyses are undertaken for native-born workers and for foreign-born workers. Analyses are presented for all workers, for young workers, and for workers categorized according to the distance or time that they travel to work. This latter set of analyses permits insights into the wage effects for workers who are trapped in local labor markets, as compared to the wage effects for workers who work in broader labor markets. Consistent with the earlier research, the paper shows that the commute to work is associated with modest wage increases in each country. Within each country there are minor variations in these wage increases by gender and nativity. Consideration of the wage effects of commute time and commute distance has little effect on the gender pay gap, which remains a sizeable feature of the pay outcomes in Canada and the United states. The changes in the labor market over the past 20 years, which include higher rates of female labor force participation, a decline in the extent of occupational segregation, a narrowing of the gender wage differential, and a major change (suburbanization) in the spatial organization of work have, therefore, had little effect on the role of the commute to work in the determination of earnings.